COMMON HUB GENES AND DRUG CANDIDATES FOR DIABETIC KIDNEY DISEASE AND NON-ALCOHOLIC FATTY LIVER DISEASE: A COMPREHENSIVE BIOINFORMATIC STUDY (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Diabetes mellitus (DM) is one of the most prevalent diseases responsible for worldwide morbidity and mortality. The kidney and liver are the most commonly affected organs resulting in diabetic kidney disease (DKD) and non-alcoholic fatty liver disease (NAFLD). However, pathophysiological mechanisms that may be common to both DKD and NAFLD have not been elaborated despite having a common underlying cause. This study aimed to identify the hub genes that are common to both DKD and NAFLD and explore the potential drugs for their treatment. Gene expression datasets for DKD and NAFLD from the gene expression omnibus database were analyzed to identify differentially expressed genes (DEGs). A functional enrichment analysis of the DEGs was done to reveal pathways important in the etiology of DKD and NAFLD. Protein-protein interaction (PPI) network was constructed and hub genes were identified. The hub genes were further analyzed to identify potentially viable drug candidates after screening. A total of 89 DEGs were found to be common between DKD and NAFLD. Functional enrichment of said DEGs found Ppar, FoxO signaling and hepatocellular carcinoma pathways to be most prevalent in DKD and NAFLD. From the PPI network, 32 common hub genes were identified. The hub genes were analyzed for interacting drugs. Finally, 9 drugs were identified as potential candidates for the treatment of both diseases. The hub genes identified can provide new insights into the common etiology of DKD and NAFLD. The potentially viable drugs may be repurposed for the treatment of both DKD and NAFLD.